Toxicological analysis of limonene reaction products using an in vitro exposure system - Anderson, Stacey E.; Khurshid, Shahana S.; Meade, B. Jean; Lukomska, Ewa; Wells, J.R. (Toxicology in vitro, 2013)
► Exposure to reaction products may produce adverse health effects. ► A combined approach may help to investigate the role of indoor contaminants. ► Additional development is necessary for these types of in vitro models. Epidemiological investigations suggest a link between exposure to indoor air chemicals and adverse health effects. Consumer products contain reactive chemicals which can form secondary pollutants which may contribute to these effects. The reaction of limonene and ozone is a well characterized example of this type of indoor air chemistry. The studies described here characterize an in vitro model using an epithelial cell line (A549) or differentiated epithelial tissue (MucilAir™). The model is used to investigate adverse effects following exposure to combinations of limonene and ozone. In A549 cells, exposure to both the parent compounds and reaction products resulted in alterations in inflammatory cytokine production. A one hour exposure to limonene+ozone resulted in decreased proliferation when compared to cells exposed to limonene alone. Repeated dose exposures of limonene or limonene+ozone were conducted on MucilAir™ tissue. No change in proliferation was observed but increases in cytokine production were observed for both the parent compounds and reaction products. Factors such as exposure duration, chemical concentration, and sampling time point were identified to influence result outcome. These findings suggest that exposure to reaction products may produce more severe effects compared to the parent compound.